The book of looms : a history of the handloom from ancient times to the present - Broudy, Eric (Waltham, Massachusetts : Brandeis University Press, 2021)
"Broudy shows how virtually every culture, no matter how primitive, has woven on handlooms. He highlights the incredible technical achievement of primitive cultures that created magnificent textiles with the crudest of tools and demonstrates that modern technology has done nothing to surpass their skill or inventiveness"--
Includes bibliographical references and index.
Keywords: Looms